Risk Controlling of Gastrointestinal Bleeding in Comorbid Patients with Cardiovascular Diseases - O. Yu. Chizhova; L. N. Belousova; I. G. Bakulin (Рациональная фармакотерапия в кардиологии)
The issues of prevention of thromboembolic complications (TE) in the management of patients with atrial fibrillation (AF) are of leading importance. Recently, non-vitamin K antagonist oral anticoagulants (NOACs), previously known as new oral anticoagulants are used in the treatment and prevention of TE in patients with AF. A lot of data has been accumulated, in which the NOACs indications have been revised. As a result, the updating has been done in the Recommendations of European Society of Cardiology (2016), the project of Russian Society of Cardiology Guidelines (2017), as well as in the new Recommendations of the European Heart Rhythm Association (2018). At the same time, the issues of prevention ща hemorrhagic complications, especially gastrointestinal bleeding, remain unresolved. Currently, there are no clinical guidelines on the use of NOACs from the standpoint of prevention of gastrointestinal bleeding, as well as definition of the risk of gastrointestinal bleeding in the treatment of NOACs. The authors analyze the recommended algorithms for the evaluation of the risk of gastrointestinal bleeding in NOACs using.